Development and mechanistic investigation of recombinant type III humanized collagen gel for mid-facial soft tissue repair - Qian Wang; Qifei An; Yuanzhou Wang; Jingbo Yang; Xiujuan Zhang; Shibo Jiang; Min Chen; Lu Lu; Yun Zhu (Collagen and Leather)
Abstract Mid-facial depression is a key sign of facial aging, primarily caused by the loss of collagen leading to depletion of the extracellular matrix (ECM). However, the existing fillers for soft tissue augmentation have shown certain limitations in repairing mid-facial depression. Therefore, we herein report the development of a novel recombinant humanized type III collagen gel (C3Gel) through rational design and modification of a commercially available recombinant type III humanized collagen lyophilized fiber product. Both biological activity and tissue repair mechanisms of C3Gel were systematically evaluated in vitro and in vivo. C3Gel formed a dense fibrous structure around cells, significantly improving the ECM environment and providing strong support for cells, thereby promoting cell adhesion, migration, and proliferation. After injection of C3Gel into the dorsal region of rats, we observed a significant increase in the expression of type I collagen and elastin that improved tissue mechanical properties and elasticity. High-throughput RNA sequencing analysis revealed that C3Gel activated the integrin signaling pathway to improve binding between cells and ECM, resulting in the increased expression of downstream genes by activating the PI3K-Akt pathway which promoted the production of ECM components, such as collagen and laminin. At the same time, the expression of matrix metalloproteinases was inhibited to maintain ECM stability. Moreover, C3Gel is not carcinogenic in mice. Therefore, C3Gel demonstrates excellent biocompatibility and significant tissue repair ability, offering a safe, efficient, and long-term stable solution for mid-facial soft tissue augmentation, while providing new insights for other applications in regenerative medicine. Graphical abstract